Does the Order of Submaximal Lactate Threshold and Maximal Oxygen Uptake Testing Influence Test Outcomes? - Torvik, Per-Øyvind; van den Tillaar, Roland; Iversen, Gaute (Sports (Basel), 2020)
The aim of this study was to investigate if the order of submaximal lactate threshold and maximal oxygen uptake testing would influence test outcomes. Twelve well-trained male cross-country skiers (mean age 19.6 years) performed two test sessions within a week in a within-subjects repeated measures with cross-over design study. A maximal oxygen uptake test (VO2max) followed by a lactate threshold (LT) test and vice versa, were performed. The test data included VO2, blood lactate (La-b), heart rate (HR), performance speed, Borg scale (RPE) at all stages and lactate accumulation throughout the whole test protocol including the breaks. No significant effect of testing order was found for: VO2max (74.23 vs. 73.91 mL∙min−1∙kg−1), maximal HR (190.7 vs. 189.9 bpm) and speed at LT during uphill running. Three out of four common definitions of LT resulted in the same La-b at the last two steps, 11 and 12 km/h respectively, in the two protocols. It is worth noting that VO2, HR and La-b were higher in the first two stages of the LT test when VO2max was tested first in the protocol. Well-trained cross-country skiers conclusively attained a similar VO2max and LT in both protocols, and the two tests did not seem to influence each other in terms of the degree of exhaustion that occurs in a single VO2max or an incremental LT test. However, when using a curvilinear function to define the LT, it is important to know that the VO2max test can influence levels of VO2, HR and La-b at the first two stages of the LT test.